2016
DOI: 10.1093/pasj/psw016
|View full text |Cite
|
Sign up to set email alerts
|

The MAXI/GSC Nova-Alert System and results of its first 68 months

Abstract: Various transient phenomena on a timescale ranging from seconds to days appear at unexpected sky positions in X-rays. MAXI, Monitor of All-sky X-ray Image, on the International Space Station has been monitoring about 95% of the sky a day and has detected transient objects since 2009 August. Here, we describe quasi-real-time data processing systems of MAXI and a subsequent nova-alert system to find transient objects, and present the capabilities for the nova-alert system to detect transient events with excess f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…The MAXI transient alert system (Negoro et al 2016) signalled activity from 4U 1608−52 on 19 June 2018 June 19 (MJD 58288; nova ID 8288849999). When MAXI monitoring indicated that 4U 1608−52 had evolved beyond its outburst peak, we started to monitor the source with the X-ray telescope (XRT) aboard the Neil Gehrels Swift observatory (Swift; Gehrels et al 2004).…”
Section: Set Up Of the Observation Programmentioning
confidence: 99%
“…The MAXI transient alert system (Negoro et al 2016) signalled activity from 4U 1608−52 on 19 June 2018 June 19 (MJD 58288; nova ID 8288849999). When MAXI monitoring indicated that 4U 1608−52 had evolved beyond its outburst peak, we started to monitor the source with the X-ray telescope (XRT) aboard the Neil Gehrels Swift observatory (Swift; Gehrels et al 2004).…”
Section: Set Up Of the Observation Programmentioning
confidence: 99%
“…Each photon direction typically has errors of 1.5 deg in the scan direction and ∼2 deg in the orthogonal direction at FWHM, corresponding to the point spread function (PSF) of the camera. A nominal GSC camera can detect transient events with a 2-20 keV flux greater than 2 ×10 −9 erg cm −2 s −1 (e.g., Serino et al 2014;Negoro et al 2016) in a scan transit. At the time of the GW170817 observation, seven cameras of ID 0, 2, 3, 4, 5, 6, and 7 were functioning (Mihara et al 2014), and the GSC observed the position using camera ID 2 on the zenith module and using camera ID 4 and 5 on the horizontal module for 10 days after the GW trigger.…”
Section: Instrumentation and Operationmentioning
confidence: 99%
“…Figure 1 shows Xray images of the GSC observation in (a) the first orbit, (b) one day, and (c) ten days with the 90% and 50% probability contours of localization by the LALInference v2 map of GW170817. The MAXI/GSC real-time transient monitor and alert system (novaalert system) is continuously operating (Negoro et al 2016). The nova-alert system detects transient events with fluxes >80 mCrab in a one-orbit scan and sends an alert to the world in less than 30 s after the onboard detection of the transient.…”
Section: Observation Of Gw170817mentioning
confidence: 99%
“…The data from 2009 August 15th to 2011 August 15th are used there. All the data they used were delivered from the MAXI database system [7].…”
Section: Maxi Monitoring Observationsmentioning
confidence: 99%